Patients with chronic pain: evaluating depression and their quality of life in a single center study in Greece - Rapti, Ekaterini (BMC Psychol, 2019)
BACKGROUND: Chronic pain constitutes one of the most common reasons for seeking health care services and may even lead to disability. Chronic pain has been associated with depression and deterioration of the quality of life. The aim of our study is to outline the burden of chronic pain in the context of a primary health care (PHC) setting in Greece and to investigate its association with depression and quality of life. METHODS: A cross-sectional study was conducted from September 2016 to November 2016. The subjects of the study comprised 200 individuals who visited the regional medical center of Ag. Theodoroi, Greece. The collected data were from a representative sample of 200 adults and included demographic data, social and medical history, presence and characteristics of chronic pain and questions from three questionnaires for the assessment of pain (BPI- short form), the investigation of depression (PHQ-9) and the evaluation of the quality of life (EuroQ-5D) validated in Greek language. Multiple regression analysis was used in order to find associated factors with quality of life, depression and chronic pain. RESULTS: A percentage of 56.8% of the participants, the majority of whom (62%) were women, reported chronic pain. Among individuals with pain, lower back area was the most common location. Based on the given questionnaire, depression was detected in 22. 5% of the participants who claimed chronic pain. Regression analyses revealed that women and respondents with chronic mental disorders like depression and anxiety had significantly higher scores on the pain scale and suffered pain which had a greater impact on their daily activities. According to regression analysis decreased quality of life was expressed by women, as well as participants with a chronic mental disorder. A significant reverse correlation emerged between the quality of life, depression and pain scales. CONCLUSION: Chronic pain, as it has been studied within this PHC setting, is a common health care problem. Individuals who had experienced chronic pain and depression had a lower health-related quality of life.